Desenvolvimento e utilização de ontologias em bibliotecas digitais: uma proposta de aplicação - Ramalho, Rogério Aparecido Sá [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Throughout the last years, the increasing use of Technologies of Information and Communication (TICs) have stimulated a new gamma of informational necessities. The digital environments favor the transposition of the conventional limits of representation and dissemination of the registered knowledge, incorporating new elements to the processes of production, organization and recovery of information. Considering the ontologies as a new and riveting category of systems of representation of knowledge, we searched, starting from a interdisciplinary dialogue, bases that allow to analyze the approaches of this new computational approach with the instruments and methods traditionally used in the area of Knowledge Organization, investigating in what scale the area of Information Science can contribute to the development of ontologies and analyzing the consequences of its use in digital libraries. Therefore, a study of the main theories and technologies related to the development of ontologies and digital libraries was carried through, contextualized in the theoretical framework of the area of Information Science. In this way, the Ontology of Referential Informations (OIR) and a prototype of a Digital Library based on ontologies, called BibliOntO, was developed with the objective of analyzing the applicability of ontologies in digital libraries. As results, it was verified that the ontologies allow the development of new types of information services and improvements in the processes of representation, organization and recovery of information in digital environments. It was also evidenced that its application in digital libraries represents an interesting alternative, contributing for an adjusted attendance of the informational necessities of the users, in a way that the ontologies consist as a new... (Complete abstract click electronic access below)

Ao longo dos últimos anos, a crescente utilização das Tecnologias de Informação e Comunicação (TICs) tem impulsionado uma nova gama de necessidades informacionais. Os ambientes digitais favorecem a transposição dos limites convencionais de representação e disseminação do conhecimento registrado, incorporando novos elementos aos processos de produção, organização e recuperação de informações. Considerando as ontologias como uma nova e instigante categoria de sistemas de representação do conhecimento, buscou-se, a partir de um diálogo interdisciplinar, fundamentos que possibilitem analisar as aproximações desta nova abordagem computacional com os instrumentos e métodos tradicionalmente utilizados no área disciplinar de Organização do Conhecimento, investigando em que medida a área de Ciência da Informação pode contribuir para o desenvolvimento de ontologias e analisando os reflexos de sua utilização em bibliotecas digitais. Para tanto, foi realizado um estudo das principais teorias e tecnologias relacionadas ao desenvolvimento de ontologias e bibliotecas digitais, contextualizando-as a partir do corpus teórico da área de Ciência da Informação. Deste modo, foi desenvolvida a Ontologia de Informações Referencias (OIR) e um protótipo de Biblioteca Digital baseado em ontologias, denominado como BibliOntO, com o objetivo de analisar a aplicabilidade de ontologias em bibliotecas digitais. Como resultados, verificou-se que as ontologias possibilitam o desenvolvimento de novos tipos de serviços de informação e melhorias nos processos de representação, organização e recuperação de informações em ambientes digitais. Constatou-se também que sua aplicação em bibliotecas digitais representa uma interessante alternativa, contribuindo para um...
Keywords: Ontologia; Ontologias (Recuperação da informação); Organização da informação; Bibliotecas digitais; Representação do conhecimento (Teoria do conhecimento); Sistemas de organização do conhecimento; Tecnologias semânticas; Ontologies; Systems of knowledge organization; Organization of information; Digital libraries; Semantic technologies